PEMBERDAYAAN SDMK PADA PENERAPAN APLIKASI PEMODELAN DATA WAREHOUSE STUNTING DI KABUPATEN KEDIRI TAHUN 2025 - Aris Dwi C.; Luluk S.; Arik Sofan T. (Indonesian Health Literacy Journal, 2025)
Empowering SDMK is crucial, as it maximizes the use of technology. SDMK with adequate skills and knowledge can effectively operate health data applications, enabling optimal utilization of all features and functions. This ensures data accuracy and sustainability, with SDMK responsible for accurately entering, verifying, and maintaining data. Therefore, the System Requirement System for designing a web-based data warehouse is intended to provide an overview of the application design that will be developed to support decision-making or policies related to handling stunting in the Population Control, Family Planning, Women's Empowerment and Child Protection Service (DP2KB3A) of Kediri Regency. The focus of the Stunting Data Management Information System is the governance of the implementation of recording and reporting of stunting data in Kediri Regency, designing an information system that manages administrative data and health examination results so that optimal data recording can be presented in public health services in Kediri Regency. Empowerment of Human Resources and Family Planning (SDMK) in the Implementation of Stunting Data Warehouse Modeling Application in Kediri Regency with the hope that stunting cases in Kediri Regency can be resolved or reduced as well as a more integrated, fast, and accurate reporting system by utilizing digital technology.